Etiology of acute respiratory infections using multiplex polymerase chain reaction in children admitted to pediatric intensive care unit: A single-centered retrospective observational study from Western India - Shivam Barchha; Lakshmi Shobhavat; Rekha Solomon; Shivanand Harnal (Wolters Kluwer Medknow Publications, 2023)
Background: Acute respiratory infections (ARIs) are an important cause of pediatric mortality-morbidity worldwide, the most common etiology being viral. This study aims to identify causative organisms for ARIs admitted in pediatric intensive care unit (PICU), when multiplex polymerase chain reaction (PCR) testing of respiratory secretions was sent; any seasonal trends detect microbiological correlation when co-infections. Subjects and Methods: This was a retrospective observational study, from July 2021 to December 2022, of children aged 1 month-18 years, whose multiplex PCR tests (nasopharyngeal, endotracheal [ET] secretion or bronchoscopic alveolar lavage [BAL]) were sent when admitted for ARI to tertiary care PICU. Results: In the study period, 372 of 1492 medical PICU admissions were ARI. Multiplex PCR of 81 respiratory secretions was sent, of which 69 (85%) were positive. Multiplex pcr sample positivity : 83% for nasopharyngeal aspirate, 78% for ET secretions, 100% for BAL samples. Forty-one percent of samples detected >1 organism. Respiratory syncytial virus (RSV)-A was the most common virus (18); other organisms included adenovirus (n = 5), influenza (n = 9), parainfluenza (n = 5), rhinovirus: 13, Pneumocystis Jerovecci (PCP): 4, Streptococcus pneumoniae: 17, pertussis: 1, and Haemophilus influenzae B: 9. ARIs were seen throughout the year with peaks in monsoon season and a peak in cases of ARI due to RSV from July to October. Of co-infections with bacteria in ET secretions and BAL samples via multiplex PCR, bacterial culture reports were sterile. Conclusions: Multiplex PCR detected organisms in 85% of ARI patients tested. Most of the ARIs getting admitted to PICU were viral in origin. RSV was the most common virus isolated showing peak from July to October, local monsoon season. With extended viral and bacterial PCR being available, mixed infections/colonization with uncertain significance are being detected.